Implementation of the Merdeka Curriculum in MTs Level: Evaluative Review of Countenance Stake Model - Yunita, Rahmah; Widihastuti (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
The Merdeka Curriculum was designed to offer flexibility and differentiated learning, yet its implementation in Islamic boarding schools faced challenges, particularly during early adoption. This study evaluated its implementation at Islamic boarding school–based Madrasah Tsanawiyah using Stake’s Countenance Evaluation Model with a descriptive quantitative approach supported by qualitative data. Participants included 35 teachers and 234 students from five Islamic boarding schools in Agam Regency, West Sumatra, selected via purposive sampling. Data were collected through Likert-scale questionnaires, document analysis, and in-depth interviews. Quantitative data were analyzed descriptively, and qualitative data underwent thematic analysis. Results showed that at the antecedents stage, human resource readiness reached 86% and infrastructure readiness 81%, despite institutional disparities and infrastructure limitations. At the transactions stage, learning implementation achieved 76%, with challenges in differentiated instruction and shifting learning paradigms. At the outcomes stage, assessment documentation and qualitative impacts scored 92%, though quantitative learning outcomes were not yet measurable. Key obstacles included limited module development, low technological literacy, facility disparities, and restricted project-based learning funding. Importantly, schools maintained Islamic identity while integrating the Merdeka Curriculum. The study recommends longitudinal research, broader samples, development of quantitative outcome measures, and strengthened systematic support to improve curriculum implementation quality. Abstrak: Kurikulum Merdeka dirancang untuk memberikan fleksibilitas dan pembelajaran yang berbeda, namun implementasinya di pesantren menghadapi tantangan, terutama pada tahap awal. Penelitian ini mengevaluasi pelaksanaan Kurikulum Merdeka di Madrasah Tsanawiyah berbasis pesantren menggunakan Model Evaluasi Countenance Stake dengan pendekatan deskriptif kuantitatif yang didukung data kualitatif. Partisipan terdiri dari 35 guru dan 234 siswa dari lima pesantren di Kabupaten Agam, Sumatera Barat, yang dipilih melalui purposive sampling. Data dikumpulkan melalui kuesioner skala Likert, analisis dokumen, dan wawancara mendalam. Data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis secara tematik. Hasil menunjukkan pada tahap antecedents, kesiapan sumber daya manusia mencapai 86% dan kesiapan infrastruktur 81%, meskipun terdapat disparitas antar lembaga dan keterbatasan fasilitas. Pada tahap transactions, pelaksanaan pembelajaran mencapai 76%, dengan tantangan dalam pembelajaran berbeda dan perubahan paradigma belajar. Pada tahap outcomes, dokumentasi penilaian dan dampak kualitatif mencapai 92%, meskipun hasil belajar kuantitatif belum dapat diukur. Kendala utama meliputi pengembangan modul, literasi teknologi terbatas, disparitas fasilitas, dan dana proyek terbatas. Pesantren tetap mempertahankan identitas Islam sambil mengintegrasikan Kurikulum Merdeka. Penelitian ini merekomendasikan penelitian longitudinal, sampel lebih luas, pengembangan instrumen kuantitatif, dan penguatan dukungan sistematis untuk meningkatkan kualitas implementasi kurikulum.